Technological Adaptation and TQM in Nanostores: Advancing Sustainable Development in Honduras - Ortega-Jimenez, Cesar H; Sabillon Palomeque, Dany N.; Melgar-Martínez, Narciso A; Calix, Flavio L. (LACCEI, 2025)
This study examines how technological adaptation and Total Quality Management (TQM) foster innovation in nanostores—an essential yet under-researched segment of smallscale retail in emerging economies. Drawing on survey data from 143 nanostore managers in Honduras, cluster analysis reveals distinct adaptation behaviors and highlights TQM’s mediating role in innovation. Findings support five hypotheses: (1) TQM enhances technological adaptation; (2) adaptation drives innovation; (3) nanostores form distinct adaptation clusters; (4) TQM mediates the adaptation–innovation link; and (5) clusters differ in innovation outcomes. Three adaptation profiles emerged—“Technology Leaders,” “Pragmatic Adopters,” and “Technology Laggers”— with higher innovation associated with more adaptive groups. From a Humanitarian Engineering perspective, nanostores function as nodes of inclusive innovation and community resilience. Integrating TQM with context-aware technologies provides a pathway for sustainable, scalable transformation. This research contributes to socio-technical systems theory in vulnerable settings and informs cross-sector strategies to support small retailers through participatory, quality-driven innovation. A strategic framework is proposed to guide future interventions. To strengthen generalizability, future research will expand to Colombia and Peru, offering cross-national insights that advance the goals of Humanitarian Engineering in Latin America.